Nonaesthetic Applications for Botulinum Toxin in Plastic Surgery. Issue 1 (July 2020) - Freeman, Matthew D.; Margulies, Ilana G.; Sanati-Mehrizy, Paymon; Burish, Nikki; Taub, Peter J.
Abstract : Background: Since their introduction to clinical medicine in 1989, botulinum toxin injections have been used for many indications. First used for nonsurgical management of strabismus, botulinum toxin injections are now widely used in plastic and reconstructive surgery for aesthetic indications; however, nonaesthetic indications of botulinum toxin have grown tremendously over the past two decades and span numerous specialties, including urology, dermatology, ophthalmology, otolaryngology, gynecology, plastic surgery, general surgery, and neurology. The present review aims to highlight nonaesthetic indications of botulinum toxin that are most relevant to the plastic surgeon with an emphasis on evidence-based practice. Methods: A PubMed search with manual reference checking was conducted to find the most relevant and influential articles on the nonaesthetic uses of botulinum toxin within the realm of adult plastic surgery. Studies were then categorized into areas of use, and quality of evidence for each category was highlighted. Results: Botulinum toxin has numerous nonaesthetic indications in plastic surgery, including for select pain-related disorders, skeletal muscle activity disorders, exocrine gland hyperfunction, wound healing, Raynaud phenomenon, abdominal wall reconstruction, and prosthetic breast reconstruction and augmentation. Although these indications have been widely reported, high-quality evidence supporting efficacy, optimal dose, and injection protocol with randomized controlled trials is lacking in many areas. Conclusions: Botulinum toxin is widely used in plastic surgery for a variety of nonaesthetic indications. Future studies should focus on investigating efficacy and best practice with high level of evidence research.